Independent Africa : the first generation of nation builders - Akyeampong, Emmanuel Kwaku (Indiana University Press, 2023)
"Independent Africa explores Africa's political economy in the first two full decades of independence through the joint projects of nation-building, economic development, and international relations. Drawing on the political careers of four heads of states: Kwame Nkrumah of Ghana, Ahmed Sékou Touré of Guinea, Léopold Sédar Senghor, and Julius Kambarage Nyerere of Tanzania, Independent Africa engages four major themes: what does it mean to construct an African nation-state and what should an African nation-state look like; how does one grow a tropical economy emerging from European colonialism; how to explore an indigenous model of economic development, a "third way," in the context of a Cold War that had divided the world into two camps; and how to leverage internal resources and external opportunities to diversify agricultural economics and industrialize. Combining aspects of history, economics, and political science, Independent Africa examines the important connections between the first generation of African leaders, and the shared ideas that informed their endeavors at nation-building and worldmaking"--